2016
DOI: 10.1093/femsle/fnw217
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and biosynthesis of 3-mercaptopropionic acid inMethanocaldococcus jannaschii

Abstract: In a non-targeted analysis of thiol-containing compounds in the hyperthermophilic methanogen Methanocaldococcus jannaschii, we discovered three unexpected metabolites: 3-mercaptopropionic acid (MPA), 2-hydroxy-4-mercaptobutyric acid (HMBA) and 4-mercapto-2-oxobutyric acid (MOB). HMBA and MOB have never been reported as natural products, while MPA is highly prevalent in aquatic environments as a result of biotic and abiotic processing of sulfur-containing compounds. This report provides evidence that HMBA and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Samples were then assayed for the presence of thiol-containing compounds using UPLC–HR-ESI–MS as preciously described. 56…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were then assayed for the presence of thiol-containing compounds using UPLC–HR-ESI–MS as preciously described. 56…”
Section: Methodsmentioning
confidence: 99%
“…LC–MS spectral data for these compounds were recorded on an AB Sciex Quadrupole MS interfaced with an Agilent 1200 series LC as previously reported. 56…”
Section: Methodsmentioning
confidence: 99%
“…1-MES was prepared from 1-chloroethane-1-sulfonyl chloride following previously described methods . The compound was converted to the B derivative and purified by preparative TLC as previously described …”
Section: Methodsmentioning
confidence: 99%
“…These analyses were accomplished by derivatization of the thiols with monobromobimane (mBBr), purification of the resulting derivative by preparative thin layer chromatography (TLC), followed by ultraperformance liquid chromatography–high-resolution electrospray mass spectrometry (UPLC–HR-ESI-MS) to identify the thiol-containing products. The procedure used was basically those described for the recent identification of 3-mercaptopropionic acid (MPA) in growth media of methanogens . The results of these experiments failed to show the presence of any labeled HSCoM in the cells but did demonstrate the presence of HSCoM in the growth media.…”
mentioning
confidence: 99%
“…Although both enzymes possessed malate dehydrogenase activity (converting oxaloacetate to ( S )-malate) [ 13 ], MJ1425 was identified as likely to be the biologically relevant ComC due to its kinetic parameters (higher V max and V max / K M for oxidation of ( R )-sulfolactate by NAD + to sulfopyruvate) and was classified as a sulfolactate dehydrogenase (EC 1.1.1.337) [ 10 , 11 ]. More recently, the M. jannaschii ComC (MJ1425) has been shown to also catalyze the NAD-dependent oxidation of 2-hydroxy-4-mercaptobutyric acid to 4-mercapto-2-oxobutyric acid, a precursor of the natural product 3-mercaptopropionic acid [ 14 ]. 3-mercaptopropionic acid is proposed to act as an alternative coenzyme M. Using a structure-based amino acid alignment, Irimia et al [ 10 ] identified three archaeal homologs to the M. jannaschii ComC (MJ1425) that should act as true sulfolactate dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%